Conservation agriculture practices and participation in Manica and Tete Maize Markets, Mozambique. (10th April 2015) - McNair, William E.; Lambert, Dayton M.; Eash, Neal S.
This paper analyses the marketing of maize and use of conservation agriculture practices (CAPs) by smallholder farmers in Mozambique. Specifically the factors associated with the likelihood households participate in maize markets as a vendor or buyer, and the subsequent quantity of maize transacted are examined. Of particular interest is the relationship between the adoption of CAPs practices and the likelihood a household sold or purchased maize and the quantity of maize exchanged. Use of CAPs may enhance the food security of smallholder farmers in this region. Households using CAPs were more likely to sell maize but less likely to purchase maize for household consumption. However, the overall quantity of maize transacted by CAPs adopters was not different from other households. Market transactions were more evenly distributed throughout the year for CAPs adopters as compared to other households whose transactions were concentrated during times when food was scarce.